VIEWS OF SAYED MUHAMMAD NAQUIB AL-ATTA’S ON DE-WESTERNIZATION OF KNOWLEDGE - Raz Mohammad Shirzad; Abdul Wahab Taib (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
in an era marked by globalization and the dominance of Western paradigms in knowledge production, the call for de-Westernization has become increasingly imperative. This research delves into the profound insights of Sayed Muhammad Naquib al-Atta, a prominent Muslim philosopher, on the de-Westernization of knowledge. Al-Atta offers a nuanced critique of Western epistemological hegemony and presents a compelling framework for reorienting knowledge towards indigenous and Islamic perspectives. Central to Al-Atta’s discourse is the recognition of the interconnectedness between knowledge and culture. He elucidates how Western epistemologies, rooted in secularism and materialism, have not only marginalized non-Western traditions but also undermined the holistic understanding of reality. Al-Atta’s advocates for a reclamation of indigenous knowledge systems, emphasizing their integral role in shaping human consciousness and fostering spiritual enlightenment.